1997
DOI: 10.1021/om961049+
|View full text |Cite
|
Sign up to set email alerts
|

Preparation,viaDouble Oxidative Addition, and Characterization of Bimetallic Platinum and Palladium Complexes:  Unique Building Blocks for Supramolecular Macrocycles.13C NMR Analysis of the Nature of the Palladium−Carbon Bond

Abstract: The high-yield preparation, by double oxidative addition, of nine novel platinum and palladium bis(trans-M(PR3)2X)aryl (M = Pt or Pd; R = PPh3 or PEt3; X = Br or I; aryl = 1,4-benzene, 4,4‘-biphenyl, 4,4‘‘-ter-p-phenyl, 4,4‘-tolane, or 4,4‘-benzophenone) complexes from the reaction of Pt(PPh3)4, Pt(PEt3)4, or Pd(PPh3)4 with the respective dihalo aromatic in toluene is described. These complexes were fully characterized by elemental analysis, mass spectrometry, and NMR (1H, 13C{1H}, and 31P{1H}) and vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 63 publications
9
71
0
Order By: Relevance
“…Another consequence of the ligand geometry is that when ligand 3 was used in the reaction with [Ru(η 6 -p-cymene)Cl 2 ] 2 , only the dinuclear complex {[Ru(η 6 -p-cymene)Cl 2 ] 2 [µ-(p-Ph 2 POC 6 H 4 ) 2 C(Me) 2 ]} was obtained [6] and attempts to ob- [11] A very interesting aspect connected with the formation of metallamacrocycles is the introduction of chirality by suitable self-assembly building blocks. In the case of 4, only the Cu I -based dinuclear macrocycle was formed with this ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Another consequence of the ligand geometry is that when ligand 3 was used in the reaction with [Ru(η 6 -p-cymene)Cl 2 ] 2 , only the dinuclear complex {[Ru(η 6 -p-cymene)Cl 2 ] 2 [µ-(p-Ph 2 POC 6 H 4 ) 2 C(Me) 2 ]} was obtained [6] and attempts to ob- [11] A very interesting aspect connected with the formation of metallamacrocycles is the introduction of chirality by suitable self-assembly building blocks. In the case of 4, only the Cu I -based dinuclear macrocycle was formed with this ligand.…”
Section: Resultsmentioning
confidence: 99%
“…solution of the neutral cis-platinum complexes 114 to the solid bistriflate monomers 124a-d 130,131 resulted in the quantitative formation of the squares 125a-d (Scheme 46), respectively, of differing topology and dimensions. 132 Interestingly, it was found that the self-assembly of macrocycle 125c was concentration dependent.…”
Section: Scheme 44 Scheme 45mentioning
confidence: 99%
“…Double oxidative addition to rigid aromatic ligands offers a unique way to direct the open coordination sites of metals (46), because nearly any desired angle can be fashioned provided the corresponding aryl halide is accessible. Presented here is a ligand-directed approach to molecular prisms, thus providing a versatile method for the construction of supramolecular structures of variable size and functionality, in high yield, and without the use of templates.…”
mentioning
confidence: 99%